On prepositions and particles: a case for lexical representation in systemic functional linguistics. Issue 2 (3rd April 2017) - Fontaine, Lise
Abstract : The focus of this paper is on lexical items which are traditionally referred to as prepositions, adverbs and particles, grouped here under the term P-items. It is argued that the relative lack of detail concerning lexical representation within systemic functional linguistics (SFL) theory means that there are some issues related to the status of lexis within the framework that require some development. As pointed out by Tucker [2009. In search of the grammarian's dream: locating lexis in a systemic functional grammar. In Stefaan Slembrouck, Miriam Taverniers, & Mieke van Herreweghe (eds), From will to well: studies in linguistics offered to Anne-Marie Simon-Vandenbergen, 415–426. Gent: Academia Press, 424]:if the theoretical principles are not fleshed out by way of description of both the actual grammatical and lexical resource of a given language, it is of little use to the majority of consumers, those who adopt it for (ultimately) the socio-semantic analysis of actual texts. By examining the treatment of P-items within the SFL framework and by drawing on the rich literature on this topic in cognitive linguistics, this paper aims to offer some proposals for integrating a more comprehensive, cognitively informed approach to lexis in SFL.